(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Emotional exhaustion the central component of burnout has emerged as a major concern for education systems worldwide, undermining teachers’ wellbeing, instructional quality, and organizational continuity. This article examines emotional exhaustion among school staff and its influence on job satisfaction with specific reference to Delhi schools. Drawing on established theoretical frameworks (including Freudenberger’s early description of burnout, Maslach’s tripartite model, and Hobfoll’s Conservation of Resources theory), empirical findings from India and international literature, and recent studies focused on Delhi, the paper traces historical and contemporary causes, mechanisms, and consequences of emotional exhaustion. Evidence suggests that high workloads, role conflict, inadequate administrative support, job insecurity among contractual staff, and poor work–life balance significantly elevate emotional exhaustion, which in turn reduces job satisfaction, increases absenteeism, and erodes teacher commitment. The article concludes with recommendations for multilevel interventions organizational reforms, professional development, mental-health supports, and policy-level changes and identifies promising avenues for future research to strengthen teacher wellbeing and school effectiveness in urban Indian contexts.